ALGORITHM FOR INDICATION OF COLLECTOR EQUIPMENT FOR STOMAS (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To report the experience of a team of enterostomal therapists in the construction of an algorithm for the indication of collecting equipment for elimination stomas. Method: Experience report, from January 2018 to September 2019, on the process of building an algorithm to indicate collecting equipment for elimination stomas. Results: Based on certain clinical characteristics (assessment parameters) and the categorization of collecting equipment (solution), an algorithm was developed to indicate collecting equipment for elimination stomas. Conclusion: It is expected that this instrument can help nurses in their professional practice regarding the choice of collecting equipment and the construction of clinical protocols.